Community Capacity as Means to Improved Health Practices and An End in Itself: Evidence from a Multi-Stage Study. (April 2013) - Underwood, Carol; Boulay, Marc; Snetro-Plewman, Gail; MacWan'gi, Mubiana; Vijayaraghavan, Janani; Namfukwe, Mebelo; Marsh, David
This three-phase study characterized, validated, and applied community capacity domains in a health communication project evaluation in Zambia. Phase I explored community capacity domains from community members' perspectives (16 focus groups, 14 in-depth interviews, 4 sites. These were validated in Phase II with 720 randomly selected adults. The validated domains were incorporated into a program evaluation survey (2, 462 adult women, 2, 354 adult men; October 2009). The results indicated that the intervention had direct effects on community capacity; enhanced capacity was then associated with having taken community action for health. Finally, community capacity mediated by community action and controlling for confounders, had a significant effect on women's contraceptive use, children's bed net use, and HIV testing. The results indicate that building community capacity served as a means to an end—improved health behaviors and reported collective action for health—and an end-in-itself, both of which are essential to overall wellbeing.